NON-VAL30MET-TRANSTHYRETIN AMYLOID CARDIOMYOPATHY. LITERATURE REVIEW AND CLINICAL CASE - A. Ya. Gudkova; A. A. Poliakova; А. V. Amelin; O. М. Moiseeva; А. N. Krutikov; V. М. Tishkova; R. V. Grozov; D. V. Ryzhkova; T. V. Makurova; A. A. Kostareva; E. N. Semernin; E. V. Shlyakhto (Российский кардиологический журнал, 2018)
A literature review presented, with a clinical observation of non-Val30Mettransthyretin amyloid cardiomyopathy. Modern diagnostic and management algorithms discussed.